Health process focused on care for neonates and children with Myeolomeningocele disease: an integrative review (Research, Society and Development, 2023)
Myelomeningocele (MMC) is an embryonic malformation of the central nervous system, which occurs in the first four weeks of pregnancy. It is due to a failure in the closure of the neural tube. Myelomeningocele is the second cause of locomotor system deficiency in children. Recent studies reveal the influence of major genetic, environmental and nutritional factors, such as folic acid deficiency in early pregnancy. It aims to observe pregnant women, newborns and children through the literature with a attentive look at the Myelomenigocele disease. The method is an integrative literature review, the databases used were SciELO, LILACS and PUBMED. After applying the inclusion and exclusion criteria, the study sample consisted of 11 articles, 77% of them were published in the year 2020 and 2021, where these studies differed with the objective of each article being observed frequently among some articles open fetal surgery to correct myelomeningocele (MMC). By carrying out this review, it was possible to show in the literature nursing care for pregnant women, newborns and children through the literature with a careful look at the Myelomenigocele disease.